Clinical Features Of Sinonasal Inverted Papilloma In Sardjito Hospital - AINISABILA, Abshari ([Yogyakarta] : Universitas Gadjah Mada, 2014)
BACKGROUND: There are 3 types of Scheneiderian Papilloma: Inverted, Exopytic, and Oncotic. The most common is inverted papilloma (87%). Inverted papilloma(IP) is uncommon benign epithelial tumor which is aggressive local invasion, high recurrence rate, and possible become malignancy. IP is marked by epithelial growth into stroma without any basement membrane destruction. Decreasing patients’ qualities of life occur in IP patients. Knowing clinical features of IP is important to suspect the disease and determine the treatment as early as possible. OBJECTIVE: To know the clinical features of IP patients in Sardjito Hospital METHOD: A descriptive observational retrospective review was performed of 21 patients with Inverted papilloma in 2011-January 2014. RESULT: Out of 21 cases studied, 16 were males and 7 were females with male to female ratio of 2:1. The highest incidence was seen in the 5th and 6th decades of life with the average age of IP was 51 years old. The principle presenting symptom was nasal obstruction and rhinorrhea in same proportion (95.24%) followed by hypo/anosmia (38.1%), facial pain (33.33%), nasal deformity (28.57%), headache (19.05%), eye problems (14.29%), and epitaxis (14.29%). IP mostly occur unilaterally (80.95%). Cavum nasi involvement was seen in all 90.48% of the cases, while sinus maxillaris in 66.67%, sinus ethmoidalis in 42.86%, sinus sphenoidalis in 28.57%, sinus frontalis in 23.81%, orbita in 14.29%, and others in 23.81% of the cases. CONCLUSION: Inverted papilloma mostly presented by nasal obstruction and rhinorrea affecting the nasal unilaterally. Majority the IP located in cavum nasi, sinus maxillaris, and sinus ethmoidalis.